Training emergency physicians in sex- and gender-based medicine: assessing attitudes of program directors and residency graduates. Issue 1 (October 2016) - Madsen, Tracy; McGregor, Alyson
Abstract Background Sex and gender influence disease presentation, treatment, healthcare access, and long-term outcomes. It is uncertain to what extent sex- and gender-based medicine (SGBM) content has been integrated into emergency medicine (EM) residency curricula. We aimed to determine if SGBM is being taught in EM residency training, if EM residency program directors (PDs) declare SGBM a curriculum priority, and if recent graduates (RGs) of EM residency programs declare SGBM as relevant to their practice. Methods Two hundred twenty-six RGs and 54 PDs of US ACGME EM residency programs completed a web-based survey. Descriptive statistics were used to describe RGs' attitudes towards whether they had received instruction in SGBM overall and in specific content areas and attitudes about the relevance of SGBM to EM practice. Descriptive statistics were also used to describe whether SGBM was considered a curriculum priority by PDs and potential barriers to implementing SGBM into curricula. Results 43.2 % of RGs felt they received adequate training on gender differences in emergent conditions. Only 16.3 % of PDs believed gender differences in disease presentation were a curriculum priority. In contrast, the majority (59.5 %) of RGs felt that gender differences in emergency conditions were relevant to their practice. PDs listed completing curricular demands (76.6 %), lack of evidence-based content (53.2 %), and lack of faculty interest (36.2 %) as the largest obstacles to curriculum integration. Conclusions Over half of the RGs of ACGME EM residencies felt that their instruction in SGBM was not adequate, and SGBM was not reported as a consistent priority among PDs.